A rare case of human pulmonary dirofilariasis with a growing pulmonary nodule after migrating infiltration shadows, mimicking primary lung carcinoma - Haro, Akira (Int J Surg Case Rep, 2016)
INTRODUCTION: Pulmonary dirofilariasis is a rare pulmonary parasitic infection by the nematode Dirofilaria immitis. It is characterized by an asymptomatic pulmonary nodule usually seen on chest X-ray. The differential diagnosis of pulmonary dirofilariasis includes other pulmonary diseases, primary lung carcinoma and metastatic lung tumor. CASE PRESENTATION: Pulmonary dirofilariasis was diagnosed in a woman who presented with interstitial pneumonia. Growth of the pulmonary nodule was detected subsequent to hemoptysis. The histological diagnosis was made based on a wedge resection performed under video-associated thoracic surgery (VATS). CONCLUSION: Pulmonary dirofilariasis often varies in its clinical course. The diagnosis is best made using wedge resection under VATS.